Ankylosing spondylitis morbidity trends in Russia and Saturday spondyloarthritis schools - Shandor Fedorovich Erdes; R M Balabanova (Научно-практическая ревматология)
The countrywide detection and notification of ankylosing spondylitis (AS) are not only late, but are frequently not even done not least due to the undertraining of physicians in this area. Objective: to define a role of special educational programs for physicians in improving the diagnosis and registration of AS on the basis of its morbidity analysis. Subjects and methods. Two levels of spondyloarthritis (SpA) schools oriented to rheumatologists and other specialists were developed. Since late 2009, more than 40 schools have been arranged in different cities and towns of the country. The primary and overall morbidities of AS were studied using the data of the Ministry of Health of the Russian Federation from 2006 to 2011 inclusive: 2006-2008 were basic years (prior to SpA educational programs) and 2009-2011 are educational years. Results. In the basic years, the overall and primary AS morbidities varied within ±10%. However, there was their growing tendency just in the first year of SpA schools (2009), which persisted in the following year (2010). By 2011, the total number of AS patients increased by 2.4 times as compared to 2008; the number of first diagnosed patients did by more than 4 times. Conclusion. In the past years, the primary and overall morbidity of AS rose drastically, which is likely to be associated with the improved diagnosis of the disease due to the optimization of a diagnostic process and to the introduction of new diagnostic and therapeutic techniques. Special SpA education programs implemented in different regions of the country, by attracting more physicians of various specialties, play a significant part in the introduction of early diagnosis of AS.